Factors Affecting the Innovative Behavior of Government Employees - Ulung Pribadi; Muhammad Iqbal; Monika Siti Aisyah (Universitas Muhammadiyah Malang, 2022)
This study examined organizational structure, culture, leadership, satisfaction, and Information and Communication Technology (ICT) adoption to predict employee innovation. This study used a survey data collection method and a purposive sampling technique of respondents who did innovative behavior in realizing good governance and providing public services. The questions were created using a Likert scale. Structural Equation Model-Partial Least Square (SEM-PLS) examined the data to determine its validity and reliability and test hypotheses and regression. This study found that organizational structure, culture, and leadership positively and significantly influenced employees’ satisfaction, with p-values of 0.000, 0.000, and 0.010, respectively. Moreover, employees’ satisfaction and ICT adoption also positively and significantly influenced employees’ innovation. Organizational structure, organizational culture, and leadership had a substantial impact on employees' satisfaction (R-square = 0.865), and employees’ satisfaction and ICT adoption substantially impacted employees' innovation (R-square = 0.887). The limitations and implications of this study are evaluated.